Blue ocean strategy in financial services? - Papa, Maura (2016)
The case is meant to give readers an overview about the concept of Blue Ocean Strategy. Throughout the text hints about what this strategy refers to are given. By knowing the traditional strategic concepts – those that are usually applied in “Red Oceans” – the reader should identify and distinguish them from the Blue Oceans concepts and tools and therefore be able to analyse the case from a different strategic perspective. Recognized examples of Blue Oceans are also given in the Appendix to the case. By learning what a Blue Ocean is, readers should then decide whether the case provided can be considered an example of it or not. The case starts with a brief description of the company, how it was created, how the founders got the idea of the innovative business model and how they developed it. The case describes a situation where the founders themselves discuss about whether their company can be considered an example of Blue Ocean or not. The case follows with other examples of well-recognized Blue Ocean Strategies, to help the reader make comparisons and decide whether the company can be considered itself as another example of it. Last, some possible questions, and suggestions on how to solve them, are provided. Here the reader can reflect again on the Red Oceans tools and see how these are differently applied in Blue Oceans kind of strategies.